Preservers for the Tsallis Entropy of Convex Combinations of Density Operators - Xiaochun Fang; Yihui Lao (Advances in Mathematical Physics)
Let H be a complex separable Hilbert space; we first characterize the unitary equivalence of two density operators by use of Tsallis entropy and then obtain the form of a surjective map on density operators preserving Tsallis entropy of convex combinations.